2017
DOI: 10.2494/photopolymer.30.431
|View full text |Cite
|
Sign up to set email alerts
|

Vapochromic Fluorescence Observed for Emitting Amorphous Molecular Materials: Synthesis and Emitting Properties of 3-{4-[Bis(4-methylphenyl)amino]phenylcarbonyl}-6-{4-[bis(4-methylphenyl)amino]phenyl}-3,5-dimethyl-3,4-dihydro-2H-pyran

Abstract: In order to create novel vapochromic fluorescent amorphous molecular materials, title compound (BBMP) was synthesized and its emitting properties in solid states were investigated as well as in solution. It was found that BBMP exhibit solvatochromic fluorescence. BBMP was also found to exhibit fluorescence in solid states, the spectrum depending upon the morphology, and to exhibit mechanochromic fluorescence due to formation of glassy state by grinding the crystalline sample. And finally, BBMP film was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…We have been studying the creation of low molecular-mass photochromic materials that readily form amorphous glasses above room temperature, that we referred to as photochromic amorphous molecular materials [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…We have been studying the creation of low molecular-mass photochromic materials that readily form amorphous glasses above room temperature, that we referred to as photochromic amorphous molecular materials [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, numerous researchers have developed organic fluorescence reagents equipped with mechanochromism and vapochromism. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Recently, we reported that N,N 0 -dipyrid-3-yl-1,4,5,8-naphthalenediimide (NDI) linked to two tris(pentafluorophenyl)borane (TPFB) (1) and N,N 0 -bis(2-aminobenzophenone)-1,4,5,8-naphthalenetetracarboxylic diimide (2) formed 2:1 and 1 : 1 complexes, respectively, with toluene as single crystals with fluorescence based on the charge transfer interaction (Fig. 1).…”
mentioning
confidence: 99%